Best practices in safety management for conventional civil construction industry in Malaysia - Ahmad, Rosli (2008)
For the past few years, poor safety records in the conventional civil construction industry has tarnished its reputation and image. In addition to that, better safety management and practices in the oil and gas construction industry as compared to conventional civil construction industry are primely due to contractual requirements and consistent drives by the clients/project owners. Hence, the aim of this study is to justify best safety practices in the oil and gas construction industry that can be adopted for the conventional civil construction industry. A total of 100 sets of questionnaire were prepared and distributed to targeted respondents from construction companies ranging from CIDB Grade G1 to G7 around localised areas such as Johor Bahru, Kuala Lumpur and part of Selangor. The feedbacks from 83 respondents were analysed using frequency and relative index analysis. Based on the survey findings, it shows an excellent trend in basic practices of construction safety management. Conversely, it shows very low commitment and concern on the importance of ERT in handling emergency situations. Finally, only 52.61% (slightly more than half) of the surveyed safety management practices implemented in the conventional civil construction industry. Overally the respondents’ perceptions are in the ‘agree’ and ‘strongly agree’ categories for the levels of key elements surveyed. Whereas they perceived ‘5-Excellent’ and only ‘3-Good’ for levels of overall safety management and practices in oil and gas and conventional civil construction industries respectively. The six (6) interview respondents have also given the similar ratings. There is a strong need for the company management to implement the improvement measures in order to further improve the construction safety management. The respondents also tend to ‘strongly agree’ that implementing all the proposed measures can improve the construction safety management, safety investment is a viable and worthy effort and safety indicators implementation is low. Among recommended safety best practices are guiding policies, certifications, good HSE plannings, programs, rules and practices, safety indicators and safety campaigns and celebrations.